Enhancing Junior High Students’ Conceptual Understanding through Humanized AR–VR Learning Media - Widyaswara, Bayu (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aimed to design and develop an interactive Augmented–Virtual Reality (AR–VR) learning medium to improve junior high school students’ conceptual understanding of the human digestive system. The research was conducted at SMP Negeri 1 Kota Batu using the ADDIE instructional design model, which includes the stages of analysis, design, development, implementation, and evaluation. Forty students participated in six classroom meetings involving AR–VR learning sessions. Data were collected through pre- and post-tests, classroom observations, and student response questionnaires. The results showed a modified N-gain score of 0.70, indicating a moderate-to-high level of improvement in students’ comprehension. The practicality score averaged 91%, suggesting that the developed media were feasible, interactive, and well-received. Students expressed enthusiasm toward the AR–VR environment created using Assemblr Edu and MilleaLab, perceiving it as intuitive and visually engaging. The novelty of this study lies in its humanized approach to integrating AR–VR technology for science learning in Indonesian junior high schools. These findings imply that AR–VR learning media can effectively foster conceptual understanding and engagement when supported by a structured instructional model such as ADDIE.